Employing SWOT Analysis to Uncover the Crucial Determinants of Academic Performance Among Non-residential Students at IAIN Lhokseumawe - Vikri Haikal, Muhammad; Husni, Talita Afifah (Islamic Educational Management Programme, 2023)
This research aims to elucidate the determinant factors that influence the performance of remote students at the State Islamic Institute (IAIN) Lhokseumawe. Framed within a descriptive qualitative research design, this study employs a case study approach as its primary data collection methodology. The underpinning factors influencing performance are gathered through an extensive document study. The findings derived from the performance study of IAIN Lhokseumawe students reveal that the determinants of student performance are influenced by both internal and external factors. The internal factor encompasses self-management (self-efficacy), while the external factors include cultural and environmental aspects. This study provides in-depth insights into how these intertwined factors contribute to the academic performance of remote students and offers a holistic understanding of the challenges and opportunities that these students encounter in their academic journey.